2021
DOI: 10.1177/00957984211037440
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Suicide Ideation: The Role of Self-Acceptance for Black Young Adults

Abstract: Suicide is a leading cause of death for Black young adults. Though depression is commonly linked to increased risk for suicide, empirical literature examining the depression–suicide association and intrinsic buffers for this association remains limited among Black young adults. This study sought to address this gap in the literature by examining the relationship between depression and suicide ideation among Black young adults. Importantly, this study assessed the moderating role of self-acceptance, an index of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Another potential explanation for this inconsistency is that both universities are minority-serving universities, and one is situated in a city with the presence of a strong Black community and subsequently potentially high self-acceptance surrounding the students of this study. Given that self-acceptance has been shown to reinforce resilience among Black youth and families (Bauermeister et al, 2007; Brooks et al, 2021; Butler-Barnes et al, 2013), a thriving Black environment is unfortunately a unique setting and may have led to a different pattern of results. Among other unexpected findings with regard to demographic variables, university emerged as a variable that was predictive of general suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential explanation for this inconsistency is that both universities are minority-serving universities, and one is situated in a city with the presence of a strong Black community and subsequently potentially high self-acceptance surrounding the students of this study. Given that self-acceptance has been shown to reinforce resilience among Black youth and families (Bauermeister et al, 2007; Brooks et al, 2021; Butler-Barnes et al, 2013), a thriving Black environment is unfortunately a unique setting and may have led to a different pattern of results. Among other unexpected findings with regard to demographic variables, university emerged as a variable that was predictive of general suicidality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that acceptance can effectively reduce one's level of depression and SI (58), and a meta-analysis has shown that ACT can reduce SI by improving one's level of acceptance and thereby improving their psychological flexibility (59). In addition, a recent study found that self-acceptance plays a moderating role between depression and SI (60). But self-acceptance is conceptually different from acceptance in ACT, and refers to the ability to think positively about yourself and your life, while acknowledging the good and bad qualities within yourself (60).…”
Section: The Moderating Role Of Acceptancementioning
confidence: 99%
“…In addition, a recent study found that self-acceptance plays a moderating role between depression and SI (60). But self-acceptance is conceptually different from acceptance in ACT, and refers to the ability to think positively about yourself and your life, while acknowledging the good and bad qualities within yourself (60). Therefore, the moderating effect of acceptance on depression and SI is still worth studying.…”
Section: The Moderating Role Of Acceptancementioning
confidence: 99%
“…It may also be helpful to examine such patterns geographically as well. Brooks et al (2023) provide the fifth article in the special issue. They focus specifically on depression and suicide ideation and the moderating role of selfacceptance in Black young adults, broader than Black youth but encompassing Black adolescents.…”
mentioning
confidence: 99%